Hydrogen bond dynamics governs the effective photoprotection mechanism of plant phenolic sunscreens. Issue 2 (16th December 2016) - Liu, Fang; Du, Likai; Lan, Zhenggang; Gao, Jun
Abstract : For the effective photoprotection in natural plant sunscreens, there is direct coupling of hydrogen bond motion with photoprotection dynamics in the condensed phase. Abstract : Sinapic acid derivatives are important sunscreen species in natural plants, which could provide protection from solar UV radiation. Using a combination of ultrafast excited state dynamics, together with classical molecular dynamics studies, we demonstrate that there is direct coupling of hydrogen bond motion with excited state photoprotection dynamics as part of the basic mechanism in solution. Beyond the intra-molecular degree of freedom, the inter-molecular motions on all timescales are potentially important for the photochemical or photophysical events, ranging from the ultrafast hydrogen bond motion to solvent rearrangements. This provides not only an enhanced understanding of the anomalous experimental spectroscopic results, but also the key idea in the development of sunscreen agents with improved photo-chemical properties. We suggest that the hydrogen bond dynamics coupled excited state photoprotection mechanism may also be possible in a broad range of bio-related molecules in the condensed phase.